Feasibility of Using Information in Real Estate Regulatory Authority Database as Urban Land Data Repository - Agarwal, Siddhant; Nanda, Triveni Prasad; Bali, Reema; Soni, Aparna (CSID Journal of Infrastructure Development, 2021)
The problem with the Indian real estate industry was of the lack of information and data, as well as a coherent and credible location for accessing the data. Another issue that plagued the sector until recently was that the market was unregulated, in which malpractices were rife. The Real Estate Regulation Act 2016 enacted by the government was a gamechanger in the real estate sector to address these issues. With the regulator coming into play, the consumers could access much information collated and make an informed decision. However, there are still several issues persists, such the credible and quick data access, complex coordination of records and approvals among multiple government departments and statutory bodies, and data not updated promptly. Therefore, this study aims to check the feasibility of an Urban Land Data Repository, drawn from the Real Estate Regulation Act 2016, by taking into account Indian four states of Uttar Pradesh, Madhya Pradesh, Haryana, and Maharashtra to identify potential data points for the proposed repository. The paper details the data points and the rationale for taking them, closing with an analysis of the current data availability for the proposed repository through this policy analysis paper.